Daybreak - Plain, Belva (New York : Delacorte Press, 1994)
In a doctor's office, a man and a woman sit stunned as the doctor speaks: Blood tests show without a shadow of a doubt that the son they love so dearly, and who is now dying, is not their child. Incredible as it seems, there must have been a mix-up in the hospital where he was born. Enduring the pain of Peter's death is a blow they must bear, but Margaret and Arthur Crawfield must also confront the realization that somewhere their biological child still lives. And although they know their search will tear apart another family, they feel compelled to look for the child who has grown up in another home.
Keywords: Cystic fibrosis -- Patients -- Fiction; Domestic fiction